Planning Model for Early Childhood Education (Pendidikan Anak Usia Dini/PAUD) and Non-Formal Education Based on National Standards Through Regional Needs Analysis in Tanah Bumbu Regency, South Kalimantan - Ambo Sakka; Ahmad Suriansyah; Hasnah Hasnah (Jurnal Pendidikan Terapan, 2026)
Purpose: This study mapped PAUD compliance with the eight National Education Standards (SNP) in Tanah Bumbu Regency and developed an evidence-based planning framework for improving institutional quality toward National Standard School status. Methods: A quantitative descriptive-analytical survey was conducted across 325 PAUD units in 12 sub-districts. Stratified purposive sampling yielded 36 nominated schools subjected to four data streams: (1) an 80-item SNP self-assessment instrument (score range 80–400); (2) Academic Ability Tests (TKA) across audio, visual, and kinesthetic domains; (3) direct Facilities and Infrastructure (SAPRAS) observation; and (4) BAN-PDM accreditation records. Weighted aggregation based on Rasch Model logit person measures (Winsteps) produced a psychometrically calibrated institutional ranking. Findings: Average SNP compliance was approximately 65.5%. The three lowest-performing standards were Facilities and Infrastructure (50%), Educator and Education Personnel (55%), and Graduate Competency (60%). Cluster analysis yielded three institutional categories: Ready, Developing, and Needs Intervention. A three-phase planning framework (2026–2030) projects overall compliance reaching 83–85% under consistent implementation. Research Implications: The gap-based framework offers a replicable model for district-level PAUD planning. Key limitations include potential social desirability bias in self-assessment data, a sampling procedure biased toward higher-performing units, and the absence of longitudinal follow-up. Originality: The study integrates multi-source triangulation with Rasch-based institutional ranking to generate a cluster-differentiated, phased planning framework advancing beyond prior district-level SNP compliance surveys by translating gap profiles directly into measurable, standards-linked KPIs.